Vital Pulp Therapy with Three Different Pulpotomy Agents in Immature Molars: A Case Report - Harandi, Azadeh; Forghani, Maryam; Ghoddusi, Jamileh (Iranian Endodontic Journal, 2013)
Introduction: This case report describes apexogenesis treatment of three molar teeth of an 8-year-old boy using three different pulpotomy agents. Methods: Pulpotomy was performed on decayed immature molar teeth with established irreversible pulpitis and the remaining pulp was capped with either zinc oxide eugenol, ProRoot mineral trioxide aggregate or calcium-enriched mixture (CEM) cement. Teeth were restored with stainless steel crowns. Results: Eighteen months clinical and radiographic follow-up revealed successful preservation of pulpal vitality with continued root development in all treated teeth. Conclusion: Based on this case report, CEM cement may be an alternative option for pulpotomy treatment of immature permanent molars.